Aggregation‐based dual‐target probe for dual‐colour super‐resolution monitoring mitophagy and evaluating drugs regulating mitochondria - Xiu‐Zhi Yang; Hongbao Fang; Shumeng Li; Chengyan Chu; Yunhua Zhang; Ying Yang; Weijiang He; Yuncong Chen; Zijian Guo (Aggregate)
Abstract Developing single fluorescent probe for simultaneously visualizing mitophagy flux and oxidative stress with super‐resolution is highly demanded yet quite challenging. Herein, a ratiometric HClO probe AHOH is designed and synthesized which is capable of simultaneously staining lysosomes and mitochondria with red and green colour, respectively. AHOH could be selectivity oxidized by HClO, leading to a large emission blue shift (90 nm) and an over 1300‐fold enhancement of the emission ratio of Fl547nm/Fl637nm. We apply AHOH in super‐resolution microscopy and clearly visualize the dynamics of mitochondria–lysosomes interactions and the oxidative stress states upon different stimuli. Mitochondria dysfunction triggered by different drugs and genetic defect lead to elevated oxidative stress and higher levels of mitophagy. Moreover, AHOH could serve as a reliable tool for evaluating the efficacy of drugs regulating mitochondria dysfunction. This work provides a powerful dual‐colour super‐resolution imaging agent for real‐time monitoring the dynamics of organelle interactions and oxidative stress.